2002
DOI: 10.1243/1468087021545504
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of hydrocarbon reduction using multiple injection in a natural gas fuelled/micro-pilot diesel ignition engine

Abstract: Research has shown that a large amount of natural gas (NG) is unburned at light loads in an NG fuelled/micro-pilot diesel compression ignition engine. A mechanism of unburned hydrocarbon (HC) reduction using multiple injections of micro-pilot diesel has been proposed in this paper. Multidimensional computations were carried out for a dual-fuel engine based on a modified CAT3401 engine configuration. The computations show that a split injection with a small percentage (e.g. 30 per cent of diesel in the second i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Two step reactions are added to code from research work published by Micklow and Gong [9]. These two reactions include: …”
Section: Combustion Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Two step reactions are added to code from research work published by Micklow and Gong [9]. These two reactions include: …”
Section: Combustion Modelmentioning
confidence: 99%
“…(13) and (14). Also six equilibrium reactions are considered in combustion process as follows [9,23,24]: Since the contribution of NO formation is greater than Nitrogen Dioxide (NO 2 ), so NO formation mechanism is studied mainly [28]. Extended Zeldovich's mechanism has been utilized for NO formation [23,24].…”
Section: Combustion Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the simulation of the combustion process inside the engine is a very complex process because it is a result of the interaction between many phenomena that occur inside the combustion chamber, such as fuel injection, vaporization, mixing, turbulent motion, ignition, and flame prorogation [6]. The combustion process with details kinetics technique obtained by CFD is essential to better understand the phenomena which occur inside the engine, resulting in the possiblity to optimize the engine parameters for drawing the maximum benefit from the dual fuel engine [13]. Kim et al [14] have investigated the effect of the gasoline ratio, the injection pressure and the intake temperature on the engine performance and emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under fixed intake air temperature conditions, increased gasoline ration in the fuel raised HC and CO emission. Lopez et al [13] investigated the effect of different gasoline and diesel blends ratio on ignition delay and flame structure for diesel engine. The results confirmed that the soot formation is affected by the flame lift-off length which is related to the fuel reactivity.…”
Section: Introductionmentioning
confidence: 99%